GaAs laser therapy reestablishes the morphology of the NMJ and nAChRs after injury due to bupivacaine - Pissulin, Cristiane Neves Alessi [UNESP]; de Souza Castro, Paula Aiello Tomï¿½; Codina, Flï¿½vio [UNESP]; Pinto, Carina Guidi [UNESP]; Vechetti-Junior, Ivan Jose [UNESP]; Matheus, Selma Maria Michelin [UNESP] (Elsevier, 2017)
Background Local anesthetics are used to relieve pre- and postoperative pain, acting on both sodium channels and nicotinic acetylcholine receptors (nAChR) at the neuromuscular junction (NMJ). Bupivacaine acts as a non-competitive antagonist and has limitations, such as myotoxicity, neurotoxicity, and inflammation. Low-level laser therapy (LLLT) has anti-inflammatory, regenerative, and analgesic effects. The aim of the present study was to evaluate the effects of a gallium arsenide laser (GaAs) on the morphology of the NMJ and nAChRs after application of bupivacaine in the sternomastoid muscle. Methods Thirty-two adult male Wistar rats received injections of bupivacaine 0.5% (Bupi: right antimere) and 0.9% sodium chloride (Cl: left antimere). Next, the animals were divided into a Control group (C) and a Laser group (LLLT). The laser group received LLLT (GaAs 904nm, 50mW, 4,8J) in both antimeres for five consecutive days. After seven days, the animals were euthanized and the surface portion of the sternomastoid muscle was removed, frozen, and subjected to morphological and morphometric analyses of the NMJs (nonspecific esterase reaction), confocal laser scanning, and an ultrastructural analysis. The nAChRs were quantified by Western blotting. Results In the chloride group, the morphology and morphometry of the NMJs remained stable. The maximum diameters of the NMJs were lower in the Bupi (15.048ï¿½ï¿½ï¿½1.985) and LLLT/Bupi subgroups (15.456ï¿½ï¿½ï¿½1.983) compared to the Cl (18.502ï¿½ï¿½ï¿½2.058) and LLLT/Cl subgroups (19.356ï¿½ï¿½ï¿½2.522) (pï¿½<ï¿½0.05). Ultrastructurally, LLLT reduced myonecrosis observed after application of bupivacaine, with recovery in the junctional folds and active zone. There was an increase in the perimeter of the LLLT/Bupi subgroup (150.33) compared to the Bupi subgroup (74.69) (pï¿½<ï¿½0.01) observed by confocal microscopy. There was also an increase in the relative planar area of the NMJ after LBI (8.75) compared to CBupi (4.80) (pï¿½<ï¿½0.01). An analysis of the protein expression of nAChRα1 showed no major differences in the groups studied. There was an increase in protein expression of the ε subunit after application of LLLT (13.055) compared to Bupi (0.251) (pï¿½<ï¿½0.01). Taken together, the present experiments indicate that there was a positive association of the α and γ subunits (pï¿½<ï¿½0.05). Conclusions These results demonstrate that LLLT at the dose used in this study reduced structural alterations in the NMJ and molecular changes in nAChRs triggered by bupivacaine, providing important data supporting the use of LLLT in therapeutic protocols for injuries triggered by local anesthetics.
Keywords: Bupivacaine; Low-level light therapy; Neuromuscular junction; Nicotinic acetylcholine receptor